Stimulation of cortical bone formation with thienopyrimidine based inhibitors of Notum Pectinacetylesterase. Issue 6 (15th March 2016) - Tarver, James E.; Pabba, Praveen K.; Barbosa, Joseph; Han, Qiang; Gardyan, Michael W.; Brommage, Robert; Thompson, Andrea Y.; Schmidt, James M.; Wilson, Alan G.E.; He, Wei; Lombardo, Victoria K.; Carson, Kenneth G.
Graphical abstract: A group of small molecule thienopyrimidine inhibitors of Notum Pectinacetylesterase are described. We explored both 2-((5, 6-thieno[2, 3- d ]pyrimidin-4-yl)thio)acetic acids and 2-((6, 7-thieno[3, 2- d ]pyrimidin-4-yl)thio)acetic acids. In both series, highly potent, orally active Notum Pectinacetylesterase inhibitors were identified. Abstract: A group of small molecule thienopyrimidine inhibitors of Notum Pectinacetylesterase are described. We explored both 2-((5, 6-thieno[2, 3- d ]pyrimidin-4-yl)thio)acetic acids and 2-((6, 7-thieno[3, 2- d ]pyrimidin-4-yl)thio)acetic acids. In both series, highly potent, orally active Notum Pectinacetylesterase inhibitors were identified.